Sacred Medieval Objects and Their Afterlives in Scandinavia - Bjerregaard, Peter; Frøysaker, Tine; Streeton, Noëlle L.W. (Early Modern History and Modern History E-Books Online, Collection 2024., 2025)
Interconnected investigations between conservators, historians, heritage scientists and museum professionals centre on objects that were essential to medieval Christianity in Scandinavia (c. 1100‒1530). Through new and diverse physical data from polychrome sculptures, shrines, winged altarpieces and painted banners, the authors probe a range of issues and problems, from original devotional functions and changing appearances, to the impacts of changing liturgies, locations and priorities, including those for curation within museums. This book highlights the diversity of theoretical and practical approaches to sacred medieval religious objects, and brings together new findings related to the transformations of these objects since the Reformations. Contributors are Karl Christian Alvestad, Alexandra Böhme, David Buti, Francesco Caruso, Aoife Daly, Tine Frøysaker, Elina Gertsman, Irka Hajdas, Poul Grinder Hansen, Karoline Kjesrud, Lena Liepe, Hana Lukasova, Maite Maguregui, Austin Nevin, Elena Platania, Anne Irene Riisøy, Katrine S. Scharffenberg, Jón Viðar Sigurðsson, Calin Constantin Steindal, Noëlle L.W. Streeton, Einar Uggerud, Anna Vila, and Jørgen Wadum. See Less